Peculiarities of Chickpea Growing Technology in the Steppe Zone of Ukraine - Zhuk Mykola; Rudenko Viacheslav; Khodjibekov S. (BIO Web of Conferences)
Chickpea is a valuable food crop. Among legumes, chickpea (Cicer arietinum) occupies a leading position in both quality and quantity of protein, which makes it a valuable food source. Its grain is widely used in human nutrition, especially in countries such as Turkey, Israel and other Middle Eastern countries. Research on chickpea breeding, seed production and cultivation technologies was carried out at the Odessa State Agricultural Research Station of the Institute of Climate-Oriented Agriculture of the National Academy of Agrarian Sciences of Ukraine from 2019 to 2022. These years provide grounds for highlighting a number of pressing issues in the modern vision of crop development. Growing demand and market prices have necessitated an increase in the cultivation area and promotion of chickpeas in the southern regions of Ukraine. Odessa region is a leader in expanding chickpea cultivation in the south of Ukraine. Several well-known farms, such as OOO AgroSvit (Belgorod-Dnestrovsky district, Petrovpavlovka village), KFH Svetlana (Bolgrad district) and others have been steadily growing chickpeas on areas of 400 to 500 hectares for the past ten years, receiving an average of 2.0–2.2 tons per hectare.